Patrick's Quest: Narration and Subjectivity in Michael Ondaatje's In the Skin of a Lion - Schumacher, Rod (Studies in Canadian Literature, 1996)
From a Lacanian poststructural perspective, narration in Michael Ondaatje's In the Skin of a Lion frames personal and collective experience. We as readers gain knowledge through narration by identifying our own position within the textual discourse. By initiating our identification with Patrick outside of a highly structured discursive community, we become dependent on his ability to provide us with the knowledge of the text. We imaginatively join with Patrick Lewis, the pivotal figure in the novel, in the quest for subjectivity.